Analisis Kesalahan Penggunaan Kara dan Node pada Siswa JLMC (Japanese Language Management Center) - Hauda, Hilwa; Danasasmita, Wawan (Chi'e: Journal of Japanese Learning and Teaching, 2021)
This article examines the use of conjunctions or setsuzokujoshi of kara and node that mean reasons in Japanese. The subjects in this study were students of the Nippo class who were studying at LPK Japanese Language Management Center (JLMC). This research uses descriptive analysis method by collecting data from students to answer 6 questions about kara and node. The results showed that students understanding about use of kara and node was good enough, with a percentage 59%. Then based on the results of the item analysis, can be seen that the students made more mistakes in kara form than node form, with the error percentage in kara reach 62% and node 21%. The main cause of students lack of understanding about the differences of kara and node is the teacher who does not explain in detail the differences between kara and node. Besides that, learning material or book that students used there is no details explanation about different of kara and node.